Where is Our Mama? - Goode, Diane (Random House UK Ltd, 1993)
A Caldecott Honor medalist offers a charming and stylish evocation of Paris as a helpful gendarme aids two children who have become separated from their mother.
Keywords: Family; Juvenile Fiction; Parents